Legal Review of Drone Use as Weapons and Surveillance Tools in Armed Conflict: An International Humanitarian Law Perspective - Lourens, Priska Marsya; Peilouw, Johanis Stenly Franko; Waas, Armelia Febrianty (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This article examines the use of unmanned aerial vehicles (drones) as weapons and surveillance tools in armed conflict. The core issue lies in the potential inconsistency between current drone practices and fundamental principles of international humanitarian law, specifically distinction and proportionality.Purposes of the Research: This research aims to analyze the legality of drone deployment in armed conflict under international humanitarian law. Methods of the Research: This research uses a normative legal method with a literature study approach, focusing on the analysis of relevant laws and international legal documents.Findings of the Research: Findings indicate that drone use can violate the principles of distinction and proportionality, often leading to disproportionate civilian casualties due to difficulties in distinguishing between military and civilian targets. Furthermore, the absence of specific international regulations on drone warfare creates a legal vacuum, increasing the risk of violations and abuse. Therefore, the study concludes that specialized regulations are urgently needed to align technological advancements with humanitarian law principles.